Mediation of work pressure on the relationship between professional compatibility and job rotation: An applied study on Bisha Electricity Company - Hamid, Adam Ahmed Musa (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aims to measure the extent to which work pressure is mediated by the relationship between professional compatibility and work turnover, and to determine the impact of work pressure on the effectiveness and efficiency of workers, to indicate the role of work pressure in work turnover. The importance of the study comes from the role of work stress and its repercussions on the performance of workers in business organizations. It also highlights the relationship between professional alignment and work turnover. A questionnaire was designed and distributed on a simple random sample of (50) individuals, representing 65% of the study population, and recovered all of them. A number of statistical methods were used to validate the hypotheses, including Pearson correlation and simple regression analysis descriptive statistics (percentages, arithmetic averages, Standard deviations) to describe the characteristics of the study sample, Multiple regression analysis to test the effect of mediating work pressure (the intermediate variable) of the relationship between occupational compatibility (independent variable) and work rotation (dependent variable). A single variance analysis was also used to test differences in workers’ perceptions of sources of work pressure attributable to personal variables. It also recommended the need to reduce the sources of work pressure related to the human resource by developing and diversifying training programs While providing requirements for a work environment that helps employees to carry out their duties in a highly efficient manner.